الفكر السياسي عند الإمام السالمي : دراسة تحليلية - ريامي، عبد الله بن سليمان بن عبد الله (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2013)
The subject of this dissertation is the discussion on the political thought, the scholarly and political roles of al-Imam al-Salimi, one of the famous Omani scholars of the 14th century Hijri. Texts relevant to the subject of this research, authored by al-Imam al-Salimi and those scholars who wrote about him have been included. Scholars who had knowledge about al-Imam al-Salimi and his political thought were interviewed and places where he lived and travelled to (for the sake of knowledge) were visited. This research discusses his background and the extent of his scholarly works and efforts in reconciliation. It also presents his political thought, which led to his success in forming an Islamic State in Oman where the ruler is elected based on shura and justice. This was done by making ba'iah to his disciple, al-Imam Salim bin Rashid al- Kharusi, and then the ba'iah went to his successor, al-Imam Mohammad bin Abdullah al-Khalili, and those who were exemplary models of his political thought. The most important result of this research is that al-Imam al-Salimi's political thought had great impact on the establishment of the Islamic State in Oman. The researcher deems it essential to consider the historical political theories of Muslim scholars from all schools of thought as this is a responsibility of Islamic universities and institutes to share in this type of study, acknowledging these influential persons and their works.